2005
DOI: 10.1159/000083153
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Approximal Caries in 5-Year-Old Swedish Children

Abstract: The aim was to assess how accurately some commonly used risk factors/risk markers (predictors) for caries development could identify children with and without approximal caries as judged from bitewing radiography. Two hundred and sixty-seven consecutive 5-year-old children from two Swedish cities participated. Three experienced dentists examined the children. The predictors were the overall dmfs (decayed, missing and filled surfaces) value (canines and molars), the number of occlusal dmfs, the frequency of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
24
3
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 39 publications
7
24
3
2
Order By: Relevance
“…sucrose [Sheiham, 2001;Zero, 2004]. However, like several other studies [Garcia-Closas et al, 1997;Anderson et al, 2005], the present study failed to show a correlation between caries experience and reported intake frequency or amount of sugar-containing products. There are several possible explanations for the lack of association between sugar intake and caries experience in the present study group.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…sucrose [Sheiham, 2001;Zero, 2004]. However, like several other studies [Garcia-Closas et al, 1997;Anderson et al, 2005], the present study failed to show a correlation between caries experience and reported intake frequency or amount of sugar-containing products. There are several possible explanations for the lack of association between sugar intake and caries experience in the present study group.…”
Section: Discussioncontrasting
confidence: 56%
“…Still many epidemiological studies fail to show that the variation in caries prevalence is explained by variations in frequency or amount of sugar intake [Garcia-Closas et al, 1997;Anderson et al, 2005]. This may reflect that disease resistance is enhanced by fluoride or possibly other protective components, such as certain foods or food supplements [Zero, 2004].…”
mentioning
confidence: 99%
“…The rationale behind these guidelines is to avoid arbitrary radiographs and thereby reduce unnecessary exposure to X-rays, which is particularly important in children [Smith, 1992]. In 5-year-olds, the diagnostic yield from adding radiography to visual/tactile examination has been investigated in several studies [Raadal and Espelid, 1992;Sköld et al, 1997;Boman et al, 1999;Espelid et al, 2001;Anderson et al, 2005]. For example, 33-55% of Swedish and Norwegian 5-year-olds, respectively, benefited from bitewing examination even though they were considered to belong to low-caries prevalence populations [Raadal et al, 2000;…”
mentioning
confidence: 99%
“…6 Nevertheless, it has been advocated that 5-year-old children should be exposed to bitewing radiography for examination of approximal surfaces. 7,8 By using these portable digital X-ray machines, children can be diagnosed radiographically and clinically in their dental units. Also, these portable digital X-ray machines can be used while children are treated under general anaesthesia or sedation.…”
mentioning
confidence: 99%